Prevalence of ultrasound-diagnosed non alcoholic fatty liver disease among rural indigenous population in Malaysian and its association with biochemical and anthropometric measures - A. K., Abdul Sattar; Suppiah, Subapriya; Mohamad Ibrahim, Ramlah; Mohamad Nasir, Nurul Nadiah; Bahari, Norafida; Abu Hassan, Hasyma; Mohamad Saini, Suraini; Ibrahim, Idris; Zakaria, Mohd Hazeman; Mahmud, Rozi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease worldwide, especially in the Western world and Asia-Pacific regions. This study was designed to determine the prevalence of NAFLD detected by sonographic assessment among the rural indigenous population in Peninsula Malaysia and its association with anthropometric and biochemical factors. Methods: A cross-sectional survey was carried out from January 2014-February 2016. Subjects were recruited among indigenous peninsula Malaysia population in rural villages, aged ≥18 years old. The survey was questionnaire-based followed by anthropometric and blood parameters measurements. All subjects underwent abdominal ultrasound assessment to screen for the presence of NAFLD. Semi-quantitative visual grading was performed to assess for mild, moderate or severe NAFLD. Results: A total of 270 subjects underwent the screening program (mean age 43.3 ±14.0 years). Approximately 53 subjects (19.6 %) were identified with NAFLD. Of those with NAFLD, approximately 83% had moderate grade of fatty liver and the remainder were diagnosed with mild grade. NAFLD was closely associated with age, body mass index (BMI), central obesity, hypertension, total cholesterol (TC), triglyceride/high density lipoprotein-cholesterol (TG/HDL-C) ratio. On multivariate logistic regression, a high BMI (≥23.0 kg/m2), central obesity, and raised TG/HDL-C ratio were independent risk factors for developing NAFLD. Conclusion: This pioneer study defines the prevalence of NAFLD among rural indigenous population in Peninsula Malaysia. Lifestyle-related diseases, such as NAFLD can affect both rural and urban communities with equal severity. High BMI, central obesity, and elevated TG/HDL-C ratio were independent risk factors for developing NAFLD.